Gambaran radiografi impaksi ektopik molar tiga disertai kista dentigerous dalam sinus maksilaris pada radiograf CBCT 3D - Nova Rosdiana; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The aim of this case report is to explain further about radiograph on impacted right maxillary third molar and canine using CBCT 3D. Case Report: A 18 year old female patient came with swelling on her upper right posterior gum. The condition was associated with pus contained in the gum. Physical examination revealed no exact abnormalities condition on her teeth. Panoramic radiograph examination showed radiopaque image surrounded by radiointermediate image in maxillary sinus. The result of 3D CBCT radiograph exhibited radioopaque image resembling tooth 18 surrounded by unilocular radiointermediate filling 2/3 maxillary sinus with well-defined border. Conclusion: CBCT is a supported examination which may help in establishing diagnosis more accurately.